Thai Nurses’ Experiences of Providing Care in Overcrowded Emergency Rooms in Tertiary Hospitals - Saowaros Kongcheep; Manee Arpanantikul; Wanpen Pinyopasakul; Gwen Sherwood (Pacific Rim International Journal of Nursing Research, 2022)
Overcrowding in emergency rooms creates difficulties for nurses in providing safe and high quality health services for patients. Investigating the experiences of nurses in overcrowded emergency rooms can build understanding of this phenomenon and help improve the quality of care provided. This Heideggerian phenomenological study explored Thai nurses’ experiences in providing care for patients in overcrowded emergency rooms in tertiary hospitals. Data were collected from in-depth interviews with 20 Thai nurses, and the interviews were recorded, transcribed, and analyzed using thematic analysis. The findings revealed four main themes: Personal and professional impacts on the nurse, Factors contributing to overcrowding, Managing overcrowded situations, and Expectations for quality care. Study findings provided rich data that develop a greater understanding of nurses while working in overcrowded emergency rooms. Nurses were unsatisfied with their ability to provide timely, quality of care. There was a shortage of nurses to deal with the high patient load, increased stress, not enough time to teach novice nurses and student nurses, and increased risk to patients who waited long times for admission or treatment. Overcrowding leads to infection risk with patients being in close proximity. Bed shortages in hospitals contribute to long waiting times for patients awaiting admission from emergency rooms. To improve the quality of care, hospitals have to reduce overcrowding by improving patient flow and providing appropriate care for patients waiting for treatment. However, government policies need to be urgently introduced to reduce overcrowding and provide sufficient staffing and equipment. Often patients attended emergency rooms for non-urgent care, adding to overcrowding and inefficient use of resources. Therefore, effective management, collaboration, teamwork, and communication among all healthcare providers need to be undertaken to ensure that ER nurses deliver more efficient care to patients.